(Resistant Starch (RS) : Formation, Preparation, and Its Physiological Effects) - Yuliasri Ramadhani Meutia (Balai Besar Industri Agro, 2010)
Resistant starch (resistant starch - RS) is one kind of starch which resistant to amylase enzyme activity. The interesting thing of this starch is the RS that can be used as source of dietary fiber, and it has several advantages compared with traditional dietary fiber in their application in various food product, such as it can be applied as a texture modifier in baked products as well as a crisping agent. RS can be prepared through heat treatment, enzyme treatment, the combination of heat and enzyme treatment, as well as by chemical treatment using distarch phosphat ester compounds. Along with increasing public attention to health, RS plays important role as functional foods, acts as a component of dietary fiber, prebiotic, preventing colon cancer, and has a hypoglycemic effect, as well as hipocholesterolemic effect.